Effect of interface orientation on the adhesion strength and fracture toughness of Ni/CrN interfaces by first-principles study. (2nd September 2021) - Wang, Miao; Liu, Gang; Luo, Xian; Levchenko, Vladimir A
Abstract: The brittleness and relatively poor adhesion properties of CrN materials have been extensively addressed by developing Ni/CrN composites with a separate Ni phase. However, conditions at the Ni/CrN interfaces, which are the key features leading to the enhanced toughness, remain poorly understood. The present work addresses this issue by investigating the effect of interface orientation on adhesion strength and fracture toughness of Ni/CrN interfaces using first-principles calculations. To this end, we build seven Ni/CrN interface models, including Ni(100)/CrN(100), Ni(110)/CrN(110), Ni(110)/CrN(111), and Ni(111)/CrN(111), with different interface orientation and stacking orders. The results demonstrate that the interface orientation plays a predominant role in determining the mechanical properties of the Ni/CrN interfaces, while the effect of stacking order can be neglected. The Ni(111)/CrN(111) interface is demonstrated to provide the greatest adhesion strength, interfacial stability, and fracture toughness among the Ni/CrN interfaces considered, and is therefore the preferred orientation for Ni/CrN composite applications.